2015
DOI: 10.1021/acsami.5b06350
|View full text |Cite
|
Sign up to set email alerts
|

Revelation of the Technological Versatility of the Eu(TTA)3Phen Complex by Demonstrating Energy Harvesting, Ultraviolet Light Detection, Temperature Sensing, and Laser Applications

Abstract: We synthesized the Eu(TTA)3Phen complex and present herein a detailed study of its photophysics. The investigations encompass samples dispersed in poly(vinyl alcohol) and in ethanol in order to explore the versatile applicability of these lanthanide-based materials. Details upon the interaction between Eu, TTA, and the Phen ligands are revealed by Fourier transform infrared and UV-visible absorption, complemented by steady state and temporally resolved emission studies, which provide evidence of an efficient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 36 publications
0
82
0
Order By: Relevance
“…Carboxy phosphine oxide (TPO), Eu(hfa) 3 (H 2 O) 2 , and Tb(hfa) 3 (H 2 O) 2 (TPO:Eu:Tb = 21:1:20, molar ratio) were added in methanol and refluxed at 333 K for 10 h (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carboxy phosphine oxide (TPO), Eu(hfa) 3 (H 2 O) 2 , and Tb(hfa) 3 (H 2 O) 2 (TPO:Eu:Tb = 21:1:20, molar ratio) were added in methanol and refluxed at 333 K for 10 h (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…TPO (0.12 g, 0.3 mmol) was dissolved in methanol (2 ml) at 323 K and Gd(hfa) 3 (H 2 O) 2 (0.24 g, 0.3 mmol) in methanol (2 ml) was added. The precipitates were filtered, washed with methanol several times, and dried in vacuo.…”
Section: Preparation Of Gd(hfa) X (Tpo) Ymentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR spectra of ETP contains large number of absorption peaks which are basically due to three constituent molecules in ETP namely phen, TTA and Eu-O, that has already been discussed in our previous report. 6 The fingerprint IR peak of TTA is observed at 1600 cm -1 which is due to asymmetric stretching mode of C=O. 37 Theonyl ring in the TTA structure points at 1413 cm -1 and 1540 cm -1…”
Section: A Structural Characterization Using Xrd and Ftirmentioning
confidence: 99%
“…[24][25][26][27] In our previous report we have demonstrated the multi-functionality of red emitting Eu(TTA) 3 Phen (ETP) complexes, in which TTA molecules absorbed the UV-A as well as UV-B part of the radiation and transfer its energy to central Eu 3+ ion, whereas Phen protect it from the interaction with water molecules and thus provides stability to the complex. 6,28 Recently, Kumar et al have reported a strong green emitting Tb(ASA) 3 Phen (TAP) complex, in which acetylsalicylic acid (ASA) serves as the UV harvesting ligands. 27 In the present work, a hybrid complex (HC) by the mixing of ETP and TAP complexes has been prepared and their structural and optical properties have been investigated in details.…”
Section: Introductionmentioning
confidence: 99%